INFLUENCING FACTORS ON STUDENTS’ CAREER INTERESTS IN ISLAMIC FINANCIAL INSTITUTIONS - Dwijayanty, Rima; Sukadwilinda, Sukadwilinda; Sopian, Isep (The International Journal of Business Review (The Jobs Review), 2019)
The development of Islamic economics in Indonesia has developed quite rapidly. One of them is the increasing number of Islamic-based financial institutions. This development certainly requires qualified human resources in the field of Islamic finance. However, the problem that occurs is the lack of graduates who are interested in a career in Islamic financial institutions. The purpose of this research is to find out and analyze the factors that influence students' career interests in Islamic financial institutions, measured by variables of Islamic knowledge, career development and compensation. This research uses descriptive and associative methods. The data used are primary data in the form of questionnaires distributed to accounting students at Sangga Buana University YPKP who have taken Islamic accounting course. Based on the results of the study, it is seen that the variables of Islamic knowledge, career development and compensation simultaneously influence 37.9% of accounting students' career interests in Islamic financial institutions